APC protein immunoexpression in colorectal adenoma and adenocarcinoma - Bourroul, Vivian Sati Oba (2013)
BACKGROUND:activation of the Wnt pathway by mutated APC gene is considered the initial event in colorectal carcinogenesis. The identification of these mutations can improve the specific treatment of the adenocarcinoma.OBJECTIVE:detect and evaluate wild-type APC protein in tissue from colorectal adenoma, adenocarcinoma and adjacent mucosa.METHODS:42 patients that underwent surgery for adenocarcinoma and 53 patients with resected adenomas were studied. Tissue samples from the adenocarcinoma were obtained from the tumor and from adjacent non-neoplastic mucosa located 10 cm from the proximal margin of the tumor. Adenoma tissue was obtained from representative areas. Blocks of tissue microarray (TMA) were submitted to immunohistochemistry with anti-APC, with readings of positivity and intensity of immunostaining and the score of immune expression of APC protein was obtained.RESULTS:the APC protein immune expression score showed a significantly lower expression of APC protein in the adenoma when compared with the adenocarcinoma (p < 0.0001) and adjacent mucosa (p < 0.0001). The APC protein immune expression score in the colorectal mucosa and adjacent to the adenocarcinoma showed no significant difference (p = 0.24).CONCLUSIONS:the finding of decreased expression of APC protein in adenoma tissue may indicate that the mutated APC gene may contribute to the changes in the adenoma-carcinoma process of carcinogenesis sequence. The strong expression of protein APC in tissues from the carcinoma and adjacent mucosa suggests that in most patients in this series, the mutation of the APC gene did not participate in the oncogenesis mechanism.